Development of Mathematics Student Worksheets Based on Contextual Teaching and Learning for Elementary School Student - Rijal, Akmal; Susilo, Agus; Mardicko, Afri (Indonesian Journal of Primary Education, 2024)
The goal of this project is to provide a high-quality, contextually-based mathematics student worksheet product in mathematics topics that meets the highest standards for validity and specificity. With stages for definition, planning, development, and distribution, the development model used in this research was modified from a 4D model. Teachers and students in grade V at SD Negeri 33 Lubuklinggau participated in this study. Interviews and validity, practicality, and effectiveness questionnaires are the data gathering tools employed in the study. The Aiken's V formula was utilized for data analysis, encompassing the phases of instrument setup, expert evaluation, assessment collection, and score computation. The interview was conducted with the aim of obtaining information from student worksheet practicality teachers and expert validation questionnaires and practicality questionnaires for teachers and students as many as 20 people. With an average score of 0.77, the evaluation of linguists, material experts, and media experts revealed that they satisfied the valid requirements. Contextual teaching and learning-based mathematics worksheets of statistical materials meet the criteria of validity, practicality, and learner-friendliness; in the meantime, the results of the teachers' and students' practicality sheet assessment revealed that the contextual teaching and learning-based mathematics student worksheet met the practical criteria with an average score of 95.8%. Contextual teaching and learning-based learning through statistical materials offer educators a theoretical framework for creating various teaching materials. Additionally, it can serve as a means of conducting follow-up research on different subjects and educational levels at every school level.